2018
DOI: 10.1155/2018/6075403
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Reprogramming of Cancer Associated Fibroblasts: The Slavery of Stromal Fibroblasts

Abstract: Cancer associated fibroblasts (CAFs) are the main stromal cell type of solid tumour microenvironment and undergo an activation process associated with secretion of growth factors, cytokines, and paracrine interactions. One of the important features of solid tumours is the metabolic reprogramming that leads to changes of bioenergetics and biosynthesis in both tumour cells and CAFs. In particular, CAFs follow the evolution of tumour disease and acquire a catabolic phenotype: in tumour tissues, cancer cells and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
139
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(143 citation statements)
references
References 107 publications
(181 reference statements)
2
139
0
Order By: Relevance
“…[51][52][53]). Considerable evidence suggests that this metabolic rewiring of metabolism in stromal cells contributes to cancer malignancies [51][52][53][54][55][56][57][58][59]. Our results suggest that as the Gleason grade increases, rewiring of glutamine metabolism in the stromal cell compartment contributes to advancing malignancy.…”
Section: Biological Importance Of Gls1 and Glutaminase II Pathway Enzmentioning
confidence: 56%
“…[51][52][53]). Considerable evidence suggests that this metabolic rewiring of metabolism in stromal cells contributes to cancer malignancies [51][52][53][54][55][56][57][58][59]. Our results suggest that as the Gleason grade increases, rewiring of glutamine metabolism in the stromal cell compartment contributes to advancing malignancy.…”
Section: Biological Importance Of Gls1 and Glutaminase II Pathway Enzmentioning
confidence: 56%
“…The crosstalk between cancer cells and TME, especially stroma cells is widely discussed, which might be the major cause of tumour progression. 87 Fu et al showed CAFs could secrete and produce the energy metabolites, such as pyruvate and ketone bodies, in order to supply cancer cells. 88 Cancer-associated fibroblasts stimulate the growth and proliferation of tumour cells.…”
Section: Reg Ul Ati On Of C An Cer-a Sso Ciated Fib Rob L a S Ts Inmentioning
confidence: 99%
“…Our data, along with studies from others (Ding et al, 2017, Xie et al, 2015, demonstrate that 2-DG (an hexokinase inhibitor) drastically decreases collagen1 production in myofibroblasts in vitro. There is emerging evidence showing that augmented glycolysis in cancer stromal cells (also call cancer associated fibroblasts) support cancer progression through secreting lactate and other glycolytic intermediates (Avagliano, Granato et al, 2018). In addition, a decrease in microenviromental pH from lactic acid accumulation has been associated with increased TGFβ activity (Kottmann, Kulkarni et al, 2012).…”
Section: Discussionmentioning
confidence: 99%